SOSOK WANITA DALAM NOVEL DENTANG-DENTING KRISTAL KARYA ANNA R . NAWANING Suatu Kajian Sosiologis - D, Zulfardi (Menara Ilmu, 2019)
This study aimed to describe the woman in the novel-Clink Clank by Anna R.Kristal Nawaming with the help of the discripline of sociology. Research using descriptivemethods. This method serves to see and describe the data contained in the novel. Theobject of the research is novel-Clink Clank by Anna R. Kristal Nawaning published ZikrulYouth, Jakarta, in 2004.Keywords: descriptive methods, sociology